1997
DOI: 10.1046/j.1365-2141.1997.312676.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and lineage involvement in t(12;21) childhood acute lymphoblastic leukaemia

Abstract: Summary. The t(12;21)(p13;q22) translocation has been described recently as the most recurrent genetic lesion in paediatric acute lymphoblastic leukaemias (ALLs). It has also been associated with B-precursor lineage involvement and good outcome.We tested 51 diagnostic paediatric ALLs and found 11 cases with molecular evidence of the t(12;21). Interestingly, amongst t(12;21) positive patients, we report three cases with hybrid phenotype, and two cases showing an aggressive and fatal disease. Our data show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The high frequency of myeloid antigen expression (i.e. CD 13 ^nd/or CD33) that was reported originally in a large series of children with ETV6-AML1 rearrangement enrolled in the German and Italian miilticentre trials was confirmed by other reports [177][178][179]. It is interesting to note that other characteristic immunophenotypic features have been described recently that are highly predictive of ETV6-AML1 rearrangement and may be implemented as a screening test for this genetic 'abnormality [296].…”
Section: B Lineage Allmentioning
confidence: 72%
“…The high frequency of myeloid antigen expression (i.e. CD 13 ^nd/or CD33) that was reported originally in a large series of children with ETV6-AML1 rearrangement enrolled in the German and Italian miilticentre trials was confirmed by other reports [177][178][179]. It is interesting to note that other characteristic immunophenotypic features have been described recently that are highly predictive of ETV6-AML1 rearrangement and may be implemented as a screening test for this genetic 'abnormality [296].…”
Section: B Lineage Allmentioning
confidence: 72%
“…& Alexander, G.J.M. (1997) We read with interest the recent report by Lanza et al (1997) relating to the poor outcome of two of their 11 TEL/AML1positive patients. Here we describe a child with relapsed acute lymphoblastic leukaemia (ALL), TEL/AML1 transcript and p16 homozygous deletion.…”
Section: Department Of Haematologymentioning
confidence: 99%
“…Rearrangement of the TEL and AML1 genes has been associated with excellent prognosis (Shurtleff et al, 1995). Nevertheless, recently some TEL/AML1-positive patients with an extremely adverse prognosis have been detected (Lanza et al, 1997). This could be related to the presence of additional molecular lesions.…”
Section: Department Of Haematologymentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, it was suggested that therapy in this group of patients was so successful that relapse never occurred (Shurtleff et al, 1995;Cayuela et al, 1996;McLean et al, 1996). Nevertheless, more recent studies have shown that relapses do occur Harbott et al, 1997;Lanza et al, 1997;Loh et al, 1998).…”
mentioning
confidence: 99%